2009
DOI: 10.1007/s00064-009-1602-1
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Subvastus-Zugang bei der Implantation von Knieendoprothesen

Abstract: 100 patients were randomized to total knee replacement via a parapatellar or subvastus approach. Radiologically, there were no differences in operative precision or leg alignment. Patients treated minimally invasively suffered less pain and achieved a higher flexion of 110 degrees versus 95 degrees 6 weeks postoperatively. However, there were two cases of delayed wound healing in this group. The surgical technique is demanding and the operating time is longer. Long-term results are still missing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hofmann et al ( 1991 ) reported an equivalent exposure compared with the parapatellar approach. However, some authors are convinced that this procedure is more difficult to perform and only provides diminished visibility of the joint surfaces (Keblish 2002 , Halder et al 2009 ). As a compromise, the midvastus approach ( Figure 4 ) has been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hofmann et al ( 1991 ) reported an equivalent exposure compared with the parapatellar approach. However, some authors are convinced that this procedure is more difficult to perform and only provides diminished visibility of the joint surfaces (Keblish 2002 , Halder et al 2009 ). As a compromise, the midvastus approach ( Figure 4 ) has been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical incision into the knee joint for total knee replacement can be done in different ways: the classical medial parapatellar approach (Cooper et al 1999 ), the subvastus approach (Erkes 1929 , Halder et al 2009 ), and as a compromise the midvastus approach. Here, the incision divides the distal part of the vastus medialis (Hube et al 2009 ), which may interrupt its innervation.…”
mentioning
confidence: 99%
“…We wish to bring to your attention to the paper ''Sub-vastus approach is more effective than a medial parapatellar approach in primary total knee arthroplasty: a randomized controlled trial'' [3], as we are somewhat puzzled the authors do not reference it.That study [3] was a prospective randomized doubleblind study, with 231 patients recruited, more than 5 times the number in van Hemert et al 's [8] study. It used robust methodology, objective and functional outcome measures, and follow-up beyond 6-12 months [3].The study by van Hemert et al [8] set out to investigate the early postoperative differences between the parapatellar and subvastus approaches, despite the evidence already available on the subject [1,[3][4][5] 9]. Van Hemert et al [8] state: ''It can be questioned whether functional differences, if any, only occur in earlier phases of recovery'' and yet only follow-up the participants for 12 weeks post-operatively.…”
mentioning
confidence: 99%
“…The study by van Hemert et al [8] set out to investigate the early postoperative differences between the parapatellar and subvastus approaches, despite the evidence already available on the subject [1, 3–5, 9]. Van Hemert et al [8] state: “It can be questioned whether functional differences, if any, only occur in earlier phases of recovery” and yet only follow‐up the participants for 12 weeks post‐operatively.…”
mentioning
confidence: 99%